THE USE OF LOCAL HISTORY MATERIAL IN THE WORK ON COLICESTIVE NUMERICAL - M.K.Jurayeva (Galaxy International Interdisciplinary Research Journal, 2021)
Students in the first Uzbek language of instruction classes experience considerable difficulty in combining numerical with name nouns, due to the interfering influence of the mother tongue. The paper presents material on the use of the text of local history in organizing work on numerical numbers.